Oxalyl retro-peptide gelators. Synthesis, gelation properties and stereochemical effects - Makarević, Janja; Jokić, Milan; Frkanec, Leo; Čaplar, Vesna; Šijaković Vujičić, Nataša; Žinić, Mladen (Beilstein Journal of Organic Chemistry, 2010)
In this work we report on gelation properties, self-assembly motifs, chirality effects and morphological characteristics of gels formed by chiral retro-dipeptidic gelators in the form of terminal diacids (1a–5a) and their dimethyl ester (1b–5b) and dicarboxamide (1c–5c) derivatives. Terminal free acid retro-dipeptides (S,S)-bis(LeuLeu) 1a, (S,S)-bis(PhgPhg) 3a and (S,S)-bis(PhePhe) 5a showed moderate to excellent gelation of highly polar water/DMSO and water/DMF solvent mixtures. Retro-peptides incorporating different amino acids (S,S)-(LeuPhg) 2a and (S,S)-(PhgLeu) 4a showed no or very weak gelation. Different gelation effectiveness was found for racemic and single enantiomer gelators. The heterochiral (S,R)-1c diastereoisomer is capable of immobilizing up to 10 and 4 times larger volumes of dichloromethane/DMSO and toluene/DMSO solvent mixtures compared to homochiral (S,S)-1c. Based on the results of 1H NMR, FTIR, CD investigations, molecular modeling and XRPD studies of diasteroisomeric diesters (S,S)-1b/(S,R)-1b and diacids (S,S)-1b/(S,R)-1a, a basic packing model in their gel aggregates is proposed. The intermolecular hydrogen bonding between extended gelator molecules utilizing both, the oxalamide and peptidic units and layered organization were identified as the most likely motifs appearing in the gel aggregates. Molecular modeling studies of (S,S)-1a/(S,R)-1a and (S,S)-1b/(S,R)-1b diasteroisomeric pairs revealed a decisive stereochemical influence yielding distinctly different low energy conformations: those of (S,R)-diastereoisomers with lipophilic i-Bu groups and polar carboxylic acid or ester groups located on the opposite sides of the oxalamide plane resembling bola amphiphilic structures and those of (S,S)-diasteroisomers possessing the same groups located at both sides of the oxalamide plane. Such conformational characteristics were found to strongly influence both, gelator effectiveness and morphological characteristics of gel aggregates.
Keywords: chiral; organogel; oxalamide; retro-peptide; self-assembly